The Pastoral Power of Technology. Rethinking Alienation in Digital Culture - Katarina Giritli Nygren; Katarina L Gidlund (tripleC: Communication, Capitalism & Critique)
The purpose of this paper is to bring Foucault’s elaboration on ‘the pastoral modalities of power’ into play in order to rethink alienation in digital culture. Pastoral power is not displacing other conceptions of power, but provides another level of analysis involved in the forging of reasonable responsible subjects willing and able to sustain other conceptions of power. We will draw particularly on the early writings of Marx and the more recent poststructuralist developments concerning hegemony and superstructure in relation to technology. Technology as such is analysed in terms of repercussions of ‘design of the machine’ in industrial technological contexts and ‘design of digital culture’ in digital technological contexts. Pastoral power not only directs our focus to the making of technologies, but also to the making of individuals capable of taking on the responsibilities of technologies. This means that it is necessary to take on the notion of effective power of ideologies and their material reality.